Taming rewilding - from the ecological to the social: How rewilding discourse in Scotland has come to include people. (December 2021) - Martin, Alison; Fischer, Anke; McMorran, Rob; Smith, Melanie
Abstract: Rewilding is a controversial concept increasingly being offered discursively as a solution to many problems of the so-called Anthropocene. Traditionally, rewilding has been strongly associated with ecological restoration, species reintroductions, and limited human presence and intervention. However, when we examined understandings and practices of rewilding in Scotland, our semi-structured interviews and document analysis drew attention to recent changes in, and the dynamics of, rewilding discourse. These highlighted interactions between calls for 'repeopling', concerns over a 'new Clearances' and reintroduction conflicts, and drivers for community empowerment and rural economic regeneration, leading to an emerging discourse which emphasized the role of people within rewilding. We identified four important new storylines in Scotland: (i) people are an essential part of rewilding; (ii) rewilding and repeopling are compatible; (iii) rewilding will transform local rural economies; and (iv) animal reintroductions are not essential for rewilding. The dynamics of the discourse were characterised by three features: (a) adaptive organisational positioning in relation to the term 'rewilding'; (b) floating signifiers and incoherence; and (c) reflexive control of the narrative. Some of the adaptive positioning appeared to be purely rhetorical. There was limited detail or practical evidence of the inclusive participation of people in rewilding decisions, or of a well-developed socio-economic rationale for rewilding. An important challenge for the development of rewilding in Scotland and elsewhere thus relates to how these human dimensions are articulated and realised without compromising the ecological potential of the concept. Highlights: Scottish rewilding discourse emphasizes the role and positioning of people. Discursive reaction to socio-economic concerns shifts ecological focus of rewilding. Storylines describe people enabling, benefiting and compatible with ecological aims. Discourse demonstrates adaptive positioning, incoherence, and reflexivity. Challenge to articulate human dimensions but not compromise ecological potential.